Le Christ en majesté du prieuré Saint-Jean-du-Grais à Azay-sur-Cher (37) : restitution du chantier peint - Amaëlle Marzais (Revue Archéologique du Centre de la France)
The mural paintings in the Saint-Jean-du-Grais priory in Azay-sur-Cher, Indre-et-Loire, have never been the subject of a technical study. The use of sinopia is rarely observed in France for paintings from the 12th and 13th centuries. The clues left on the paintings and the drawing conducted to propose a restitution of the painting process. The study shows that the iconographic programme was scrupulously designed before it was applied to the wall. This painting illustrates the technical and stylistic changes that took place from the second half of the 12th century to the beginning of the 13th.